Effect of ZnSO4 fortification in soil on growth characteristics, phytochemicals and mineral compositions in mentha cordifolia opiz., Kitchen Mint - Timaporn Srirattanakul (Prince of Songkla University., 2018)
Thesis (M.Sc. (Functional Food and Nutrition))--Prince of Songkla University, 2016